A distinctive oral phenotype points to FAM20A mutations not identified by Sanger sequencing. Issue 6 (4th October 2015) - Poulter, James A.; Smith, Claire E. L.; Murrillo, Gina; Silva, Sandra; Feather, Sally; Howell, Marianella; Crinnion, Laura; Bonthron, David T.; Carr, Ian M.; Watson, Christopher M.; Inglehearn, Chris F.; Mighell, Alan J.
Abstract: Biallelic FAM20A mutations cause two conditions where Amelogenesis Imperfecta (AI) is the presenting feature: Amelogenesis Imperfecta and Gingival Fibromatosis Syndrome; and Enamel Renal Syndrome. A distinctive oral phenotype is shared in both conditions. On Sanger sequencing of FAM20A in cases with that phenotype, we identified two probands with single, likely pathogenic heterozygous mutations. Given the recessive inheritance pattern seen in all previous FAM20A mutation‐positive families and the potential for renal disease, further screening was carried out to look for a second pathogenic allele. Reverse transcriptase‐PCR on cDNA was used to determine transcript levels. CNVseq was used to screen for genomic insertions and deletions. In one family, FAM20A cDNA screening revealed only a single mutated FAM20A allele with the wild‐type allele not transcribed. In the second family, CNV detection by whole genome sequencing (CNVseq) revealed a heterozygous 54.7 kb duplication encompassing exons 1 to 4 of FAM20A . This study confirms the link between biallelic FAM20A mutations and the characteristic oral phenotype. It highlights for the first time examples of FAM20A mutations missed by the most commonly used mutation screening techniques. This information informed renal assessment and ongoing clinical care. Abstract : We identified two recessive Amelogenesis Imperfecta families in whom monoallelic FAM20A mutations were identified by Sanger sequencing of genomic DNA. Further screening by reverse‐transcriptase PCR and CNV detection by whole genome sequencing (CNVseq) was required in order to identify the second mutation in each case. Our study highlights the presenece of FAM20A mutations which would be missed by commonly used mutation screening techniques. This finding has important consequences for ongonig clinical care and renal assessment for both families.